Impact of second-line antiretroviral regimens on lipid profiles in an African setting: the DART trial sub-study - Gomo, Zvenyika AR (BioMed Central, 2014)
BACKGROUND: Increasing numbers of HIV-infected patients in sub-Saharan Africa are exposed to antiretroviral therapy (ART), but there are few data on lipid changes on first-line ART, and even fewer on second-line. METHODS: DART was a randomized trial comparing monitoring strategies in Ugandan/Zimbabwean adults initiating first-line ART and switching to second-line at clinical/immunological failure. We evaluated fasting lipid profiles at second-line initiation and ≥48 weeks subsequently in stored samples from Zimbabwean patients switching before 18 September 2006. RESULTS: Of 91 patients switched to second-line ART, 65(73%) had fasting samples at switch and ≥48 weeks, 14(15%) died or were lost <48 weeks, 10(11%) interrupted ART for >14 days and 2(2%) had no samples available. 56/65(86%) received ZDV/d4T + 3TC + TDF first-line, 6(9%) ZDV/d4T + 3TC + NVP and 3(5%) ZDV + 3TC with TDF and NVP. Initial second-line regimens were LPV/r + NNRTI in 27(41%), LPV/r + NNRTI + ddI in 33(50%) and LPV/r + TDF + ddI/3TC/ZDV in 6(9%). At second-line initiation median (IQR) TC, LDL-C, HDL-C and TG (mmol/L) were 3.3(2.8-4.0), 1.7(1.3-2.2), 0.7(0.6-0.9) and 1.1(0.8-1.9) respectively. Levels were significantly increased 48 weeks later, by mean (SE) +2.0(0.1), +1.1(0.1), +0.5(0.05) and +0.4(0.2) respectively (p < 0.001; TG p = 0.01). 3% at switch vs 25% 48 weeks later had TC >5.2 mmol/L; 3% vs 25% LDL-C >3.4 mmol/L and 91% vs 41% HDL-C <1.1 mmol/L (p < 0.001). Similar proportions had TG >1.8 mmol/L (0 vs 3%) and TC/HDL-C ≥5 (40% vs 33%) (p > 0.15). CONCLUSION: Modest lipid elevations were observed in African patients on predominantly LPV/r + NNRTI-based second-line regimens. Routine lipid monitoring during second-line ART regimens may not be warranted in this setting but individual cardiovascular risk assessment should guide practice.